2008
DOI: 10.1210/me.2007-0513
|View full text |Cite
|
Sign up to set email alerts
|

Role of the GATA Family of Transcription Factors in Endocrine Development, Function, and Disease

Abstract: The WGATAR motif is a common nucleotide sequence found in the transcriptional regulatory regions of numerous genes. In vertebrates, these motifs are bound by one of six factors (GATA1 to GATA6) that constitute the GATA family of transcriptional regulatory proteins. Although originally considered for their roles in hematopoietic cells and the heart, GATA factors are now known to be expressed in a wide variety of tissues where they act as critical regulators of cell-specific gene expression. This includes multip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
250
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 241 publications
(255 citation statements)
references
References 223 publications
4
250
1
Order By: Relevance
“…Therefore, our results do not suggest a key role of GATA6 in the specific beta cell lineage, but these results would need further investigation as they are limited to gene expression analyses. In mice, in which GATA6 has been further studied, expression-based analyses suggest that GATA6 could play a role in very early pancreas specification [6][7][8]. Nevertheless, it has been reported that transgenic mouse embryos expressing a GATA6-engrailed dominant repressor fusion protein in the pancreatic epithelium and in islets revealed two distinct phenotypes, either pancreatic agenesis or a simple reduction in pancreatic tissue [6], implying a putative spectrum of phenotypes, as we noted in our Intra-uterine growth retardation…”
mentioning
confidence: 44%
“…Therefore, our results do not suggest a key role of GATA6 in the specific beta cell lineage, but these results would need further investigation as they are limited to gene expression analyses. In mice, in which GATA6 has been further studied, expression-based analyses suggest that GATA6 could play a role in very early pancreas specification [6][7][8]. Nevertheless, it has been reported that transgenic mouse embryos expressing a GATA6-engrailed dominant repressor fusion protein in the pancreatic epithelium and in islets revealed two distinct phenotypes, either pancreatic agenesis or a simple reduction in pancreatic tissue [6], implying a putative spectrum of phenotypes, as we noted in our Intra-uterine growth retardation…”
mentioning
confidence: 44%
“…However, GATA4 is expressed in the developing ovary as well as in adult granulosa and thecal cells (5), which suggests that either the p.Gly221Arg mutation specifically impairs testicular development or that ovarian development may be less sensitive than the testis to reduced GATA4 activity. siGata4 transgenic mice support the latter hypothesis, where the reduction of Gata4 expression in the testis is accompanied by a significant reduction of GATA4 downstream target genes.…”
Section: Discussionmentioning
confidence: 99%
“…Briefly, TF-array-I was incubated with 5 lg of recombinant SRAP protein (ProMab Biotechnologies Inc., Albany, CA) or without (control blot) for 2 h at room temperature. Immunodetection was performed using a primary anti-SRAP antibody (targeting aa [20][21][22][23][24][25][26][27][28][29][30][31][32][33][34] and chemiluminescence signals were captured and analyzed as described [6]. For both control and samples blots, intensity of the area (in counts/mm 2 ) encompassing the two spots corresponding to each transcription factor was first corrected by subtracting the signal of an immediately negative adjacent area (local background).…”
Section: Transcription Factor Protein Arraymentioning
confidence: 99%
“…Beside steroid receptors, several other transcription factors such as FOS [27], GATA1 [32] and ETS1 [10], known to participate in critical normal developmental steps or to events underlying tumorigenesis, directly interact with SRAP (Table 1). It is of interest that an interaction has been observed between SRAP and HAND1, essential to heart development [13].…”
Section: Srap Interacts With Multiple Transcription Factorsmentioning
confidence: 99%